Pengaruh Kualitas Produk Terhadap Minat Beli Konsumen Pada Home Industri Pia Deisy Desa Kapitu Kecamatan Amurang Barat - Karundeng, Nikita; Kalangi, Johnny A. F.; Walangitan, Olivia F. C. (JURNAL ADMINISTRASI BISNIS (JAB), 2019)
This study aims to determine whether Product Quality has an effect on Consumer Buying Interest. Speaking with quality and buying interest is certainly very tied to marketing. The essence of marketing according to Daryanto (2011) "marketing is a social and managerial process where individuals and groups get their needs and desires by creating, offering, and exchanging something of value with each other". This type of research is quantitative research with data analysis techniques using a skla likert research instrument, test validity, reliability, simple linear regression analysis and hypothesis testing. Based on the results of the study the influence of product quality is a variable that does not affect consumer buying interest. Then it can be concluded that product quality does not significantly influence consumer buying interest. If the quality of the product is good, there will be buying interest and consumers will feel satisfied. In this case, Pia Deisy's business must further improve product quality so that it will be more attractive and will have a good impact on Pia Deisy's home business.